(x-100)(200-.5x)=0

Simple and best practice solution for (x-100)(200-.5x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-100)(200-.5x)=0 equation:


Simplifying
(x + -100)(200 + -0.5x) = 0

Reorder the terms:
(-100 + x)(200 + -0.5x) = 0

Multiply (-100 + x) * (200 + -0.5x)
(-100(200 + -0.5x) + x(200 + -0.5x)) = 0
((200 * -100 + -0.5x * -100) + x(200 + -0.5x)) = 0
((-20000 + 50x) + x(200 + -0.5x)) = 0
(-20000 + 50x + (200 * x + -0.5x * x)) = 0
(-20000 + 50x + (200x + -0.5x2)) = 0

Combine like terms: 50x + 200x = 250x
(-20000 + 250x + -0.5x2) = 0

Solving
-20000 + 250x + -0.5x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
-0.5 the coefficient of the squared term: 

Divide each side by '-0.5'.
40000 + -500x + x2 = 0

Move the constant term to the right:

Add '-40000' to each side of the equation.
40000 + -500x + -40000 + x2 = 0 + -40000

Reorder the terms:
40000 + -40000 + -500x + x2 = 0 + -40000

Combine like terms: 40000 + -40000 = 0
0 + -500x + x2 = 0 + -40000
-500x + x2 = 0 + -40000

Combine like terms: 0 + -40000 = -40000
-500x + x2 = -40000

The x term is -500x.  Take half its coefficient (-250).
Square it (62500) and add it to both sides.

Add '62500' to each side of the equation.
-500x + 62500 + x2 = -40000 + 62500

Reorder the terms:
62500 + -500x + x2 = -40000 + 62500

Combine like terms: -40000 + 62500 = 22500
62500 + -500x + x2 = 22500

Factor a perfect square on the left side:
(x + -250)(x + -250) = 22500

Calculate the square root of the right side: 150

Break this problem into two subproblems by setting 
(x + -250) equal to 150 and -150.

Subproblem 1

x + -250 = 150 Simplifying x + -250 = 150 Reorder the terms: -250 + x = 150 Solving -250 + x = 150 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '250' to each side of the equation. -250 + 250 + x = 150 + 250 Combine like terms: -250 + 250 = 0 0 + x = 150 + 250 x = 150 + 250 Combine like terms: 150 + 250 = 400 x = 400 Simplifying x = 400

Subproblem 2

x + -250 = -150 Simplifying x + -250 = -150 Reorder the terms: -250 + x = -150 Solving -250 + x = -150 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '250' to each side of the equation. -250 + 250 + x = -150 + 250 Combine like terms: -250 + 250 = 0 0 + x = -150 + 250 x = -150 + 250 Combine like terms: -150 + 250 = 100 x = 100 Simplifying x = 100

Solution

The solution to the problem is based on the solutions from the subproblems. x = {400, 100}

See similar equations:

| 2e-16=42 | | 3j^2+8j-4=0 | | 3x+9=4x-1 | | 5d-2=2d+3 | | 4m^2-5m+1=0 | | 5d-2=2d | | 18=2x^2 | | 3x+1=x+19 | | 6s^2-4s-4=0 | | 4(3-x)+9=7(2+x)+29 | | 7p+15-5p+10=-17+13p | | (-9x)+6-3x+(-18)=12 | | 6k^2-4k-9=0 | | 23x+26=49 | | 5g-18+2g+13=g+19 | | 7g^2+2g-3=0 | | 26.722-3.9v=-7.4(1.2+7.4v) | | -2n+22=6-7(n-8) | | 3w^2+7w-2=0 | | 9x-5=301 | | -8(3x+1)=-2x+14 | | 3x+15-6x-10=x+1 | | v^2+14v=41 | | 108r^2-147= | | 4x+(86400-4x)=86400 | | 5(x+2)=2(x-4) | | 87+x=179 | | 15-6n=15-6n | | -4n=-2-2(n-3) | | x*2+13x=-40 | | 2(4x-13)=2x+4 | | 87-4x=43 |

Equations solver categories